Implications of Correlation between Demographic Dynamics to Public Trust in Administration of Pakistan - Bajwa, Ali Abdullah; Lin, Zhou Lu; Wahla, Naveed Ahmed (Asian Journal of Social Sciences and Management Studies, 2016)
This paper highlights the issues facing the public administration of the Government of Pakistan by correlating public trust with multiple demographic variables. The aim was to determine the strength of the relationship between trust and demographic variables. A questionnaire distributed to the general public was used to judge the strength of the relationship between trust in government and different demographic indicators. Cross tabulation was used to give a better description of the data. Different measures of cross tabulation were used to determine the strength of the relationship between the variables. The performance on each variable was correlated with trust not only to determine the strength of the relationship between each demographic variable and trust, specifically for Pakistan but also to highlight areas where administrative performance was lacking. The results showed that similar to research done in other countries most of the factors mentioned in literature, such as income and religion did have a strong relationship with trust, however, age seemed not to have a significant relationship with trust in Pakistan. The research provides a general framework which will help increase trust of the public in the government, which is of utmost important to improve the ability of the Pakistani public administration to deliver goods and services to the general public.